PENDIDIKAN DI INDONESIA PADA MASA JEPANG - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
Implementation of education in Indonesia during the Japanese period has implications on various types and levels of education. The progress of educational institutions during the Japanese period can be seen in terms of the establishment of madrassas and boarding schools in remote areas, remote villages. Curriculum and methodology of education in Indonesia during the Japanese curriculum changes, namely the eradication of the curriculum of teaching dualism and the inclusion of Indonesian and Japanese language teaching curriculum, as well as funding assistance for the improvement of education curriculum. The educational methods applied are classical methods and teaching methods. Classical methods, held in schools, and teaching methods are applied in boarding schools.